A Potential Role for Substance P and Interleukin‐6 in the Cerebrospinal Fluid of Cavalier King Charles Spaniels with Neuropathic Pain. (22nd April 2013) - Schmidt, M.J.; Roth, J.; Ondreka, N.; Kramer, M.; Rummel, C.
Abstract : Background: Neuropathic pain can be a clinical sign in Cavalier King Charles Spaniels (CKCS) with syringomyelia. The pathophysiology of this pain is not fully understood. Hypothesis: Neuropathic pain in CKCS is a result of a neuroinflammatory process. Animals: Twenty‐six client‐owned dogs: 15 dogs with clinical signs of cervical hyperesthesia (group 1), and 11 dogs without of clinical signs (group 2). Methods: Dogs were examined by magnetic resonance imaging (MRI). Interleukin‐6, tumor necrosis factor alpha, and substance P were measured in CSF and compared with morphological findings on MRI and clinical pain scores. Results: All dogs without clinical signs had symmetrical syringomyelia, whereas in the group with pain, 6 dogs had symmetrical and 9 dogs had asymmetrical syringomyelia. Pain and syringomyelia asymmetry were correlated, and a strong association between pain and dorsal horn involvement of syringomyelia was observed. There was no significant difference between the mean width of the syringomyelia in dogs with or without pain. The concentrations of interleukin‐6 and substance P were significantly higher in dogs with neuropathic pain. Tumor necrosis factor alpha was not detected in either group. Concentrations of substance P were significantly higher in dogs with asymmetrical syringomyelia or dorsal horn involvement, whereas interleukin‐6 concentrations were not significantly different between groups. Conclusion: Release of interleukin‐6 and substance P may initiate proinflammatory effects leading to development of persistent pain in CKCSs with syringomyelia.